2018
DOI: 10.3310/hta22690
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose computed tomography for lung cancer screening in high-risk populations: a systematic review and economic evaluation

Abstract: BackgroundDiagnosis of lung cancer frequently occurs in its later stages. Low-dose computed tomography (LDCT) could detect lung cancer early.ObjectivesTo estimate the clinical effectiveness and cost-effectiveness of LDCT lung cancer screening in high-risk populations.Data sourcesBibliographic sources included MEDLINE, EMBASE, Web of Science and The Cochrane Library.MethodsClinical effectiveness – a systematic review of randomised controlled trials (RCTs) comparing LDCT screening programmes with usual care (no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(130 citation statements)
references
References 165 publications
5
123
0
2
Order By: Relevance
“…35 A review of this and other trials has shown considerable variation in outcomes relevant to the balance of benefits, harms and cost-effectiveness, such as screening rates, false-positive rates and lung cancer detection rates, all of which are sensitive to the screening regimen and target population. 54 The recently commenced International Lung Screen Trial in Australia and Canada 55 will provide essential information on screening a high-risk Australian cohort, and aid in identifying an acceptable cost-effective screening program in Australia.…”
Section: Lung Cancermentioning
confidence: 99%
“…35 A review of this and other trials has shown considerable variation in outcomes relevant to the balance of benefits, harms and cost-effectiveness, such as screening rates, false-positive rates and lung cancer detection rates, all of which are sensitive to the screening regimen and target population. 54 The recently commenced International Lung Screen Trial in Australia and Canada 55 will provide essential information on screening a high-risk Australian cohort, and aid in identifying an acceptable cost-effective screening program in Australia.…”
Section: Lung Cancermentioning
confidence: 99%
“…In recent years, a series of CEAs for European countries have been published: in Germany, two studies found an incremental cost-effectiveness ratio (ICER) of €19,302 per life year (LY) gained (€30,241 per QALY) and €16,754-23,847 per LY [172,173]; in the UK, two studies found an ICER lower than £11,000 per QALY [39,174], whereas the most recent study found an ICER between £20,000 and £30,000 per QALY, but under extreme assumptions, such as very small cost advantage in treating Stages I and IV and no increase in average survival between the screening and no-screening scenarios [175]; in Poland, an ICER of €1353 per LY gained was found [176]. For Italy, our simulation-based model populated with real-world cost data from hospital records found an ICER of €3297 per QALY gained and €2944 per LY gained [177]: note that this is the most recent study in this sense, and it included immunotherapy for the treatment of Stages III and IV.…”
Section: Cost-effectiveness Of Mass Ldct Screening For Lung Cancer-a mentioning
confidence: 96%
“…Systematic reviews have found significant heterogeneity in methodology and results of economic evaluations of lung cancer screening 14 15. Several researchers have analysed the cost-effectiveness of CT screening based on the NLST.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent systematic reviews of cost-effectiveness analyses of Lung Cancer Screening concluded that it is still unclear whether or not low dose CT screening is cost effective 14 15. Several things can influence cost-effectiveness estimates among other: overdiagnosis, lead-time bias, the at-risk population, the characteristics of a smoking cessation programme and incidental findings 14 15. Only one study included incidental findings 15 17…”
Section: Introductionmentioning
confidence: 99%